Reproducibility Problems of Amyloid-β Self-Assembly and How to Deal With Them - Faller, Peter; Hureau, Christelle (Frontiers in Chemistry, 2021)
The self-assembly of peptides and proteins into amyloid fibrils and other aggregates are linked to several diseases. One of the most studied cases is the peptide amyloid-β (Aβ), found self-assembled in Alzheimer’s disease patients' brains. In test tubes, assays with chemically synthesized or recombinant Aβ are widely investigated to understand the aggregation process and to find modulators, which could be of therapeutic interest. Experience over more than a decade in our laboratory, by discussions with colleagues, expertly studying the literature, and as reviewers revealed to us the widely encountered difficulty to control the aggregation and obtain reproducible results in the test tube. However, this issue is scarcely reported and discussed in the publications, which we think hampers strongly the progress in this field and can deceive newcomers. Here, we describe the difficulty and potential reasons to obtain reproducible aggregation data and propose some guidelines for working with it..